Pengaruh Profitabilitas dan Good Corporate Governance Terhadap Penghindaran Pajak - Maharani, Eriza Nabila Maharani; Akbar, Fajar Syaiful Akbar (UMSurabaya Publishing, 2025)
This study looks at how tax avoidance in real estate and property firms listed on the Indonesia Stock Exchange is impacted by profitability and good corporate governance (GCG) from 2020 to 2023. Secondary data from yearly financial reports is used in the study. 92 observations from 23 companies were obtained using a purposive sample strategy. The data was subjected to multiple linear regression analysis using SPSS 27 software. The findings indicate that tax avoidance is significantly impacted negatively by profitability, suggesting that greater profitability is linked to a lower likelihood of tax avoidance. In contrast, the audit committee used as a GCG indicators has a considerable positive association with tax avoidance. Meanwhile, the other two GCG indicators, institutional ownership and the proportion of independent commissioners, did not significantly affect on tax avoidance. These data suggest that not all aspects of GCG are effective in reducing tax avoidance. As a result, each governance mechanism's supervision functions must be strengthened in order to effectively deter tax avoidance in the property and real estate sectors.